Fatigue-resistant design in low-cycle regime by regulating the micro-structural gradient in a TWIP steel: Modelling and experiment. (December 2022) - Shao, Chenwei; Zhang, Xinqiang; Zhao, Shuo; Zhu, Yankun; Yang, Huajie; Tian, Yanzhong; Zhang, Zhenjun; Zhang, Peng; An, Xianghai; Zhang, Zhefeng
Highlights: A two-stage constitutive LCF crack growth model was proposed and developed for graded structures. A hard core & soft shell design strategy was proposed to prolong the LCF life of TWIP steel. Novel preparing methods were proposed to constructing microstructural gradual and sharp gradients in TWIP steel. A method of quantitatively evaluating LCF crack length (evolution) from the cyclic stress response curve was proposed. Abstract: It remains an intricate problem how to enhance low-cycle fatigue (LCF) performance, in the premise of guaranteeing a relatively high strength (or cyclic stress) which is vital to long-time service, for engineering components. The underlying cause of this puzzle is the lack of practical theory on cracking evolution/life prediction for LCF. In this study, a two-stage constitutive LCF crack growth model was proposed for a homogeneous solid and later developed for graded structures. Based on the model, a material design strategy emphasizing the strength gradient architecture (informally, hard core and soft shell structure) is proposed and analyzed to improve the LCF properties of engineering structural materials, e.g., steels. Experimentally, sharp and gradual strength gradients were carefully introduced into a TWIP steel by a series of well-designed process combinations regarding various (heterogeneous) deformation and annealing treatments. The influences of strength/microstructure and their spatial distributions on the LCF behaviors were systematically investigated. The excellent LCF properties of the TWIP steel with a negative strength gradient are originated from the repeated strengthening and weakening of strain gradient during cyclic loading, which suppresses the fatigue crack initiation and growth. The crack initiation/propagation model developed in this study is conducive and applicable to the LCF life prediction. The theory and process of constructing microstructure gradient, and therefore mechanical property gradient, may provide new and important implications for engineering metals on anti-LCF design.